Bid'ah as an Approach in Creating Creative and Innovative Muslim Society - Muhammad Mustaqim Mohd.Zarif; Mohd Azmir Mohd Nizah; Anita Ismail; Adibah Mohamad (Universiti Sains Islam Malaysia, 2024)
This paper is a preliminary study on the concept of Islamic creativity, innovation and its relation with bid'ah. It is undeniable that there is a link between bid'ah and the advancement of Islamic civilization. This paper also aims to reassess the conceptual and understanding of bid 'ah and its role in creating creative and innovative Muslim society. The paper further discusses the necessity of understanding bid 'ah positively as highlighted in the approach of 'duna frat wa la tafrit' in realization of Ummatan Wasatan (a just and balanced Muslim society). The study employs qualitative method with content analysis approach by evaluating the necessary and relevant reports, articles and texts. It is hoped that this preliminary paper will provide a distinctive perspective of bid'ah and its role in creativity and innovation as well as its significance in contemporary Muslim society.